Magnitude of acute respiratory infections in 6 months- 6 years in a rural hospital in B G Nagara: a cross-sectional study - Dr Shivaprakash N.C.; Dr Divya Narayanan Kutty (Pediatric Review: International Journal of Pediatric Research, 2017)
Background: ARI is a major cause for morbidity and mortality in under five children and is responsible for 30-50% of all outpatients and 20-40% of in-patients. The overall incidence may be 5 episodes/child/year accounting for about 238 million attacks.Objectives: To study the prevalence of ARI in 6 months- 6 years children in a rural hospital in B G Nagara.Methods: A cross-sectional study was conducted for a period of one year in a rural hospital. Symptoms of cough, cold, fever, refusal of feeds and hurried breathing were considered to assess an ARI episode. Respiratory rate >60/minute (<2 month infants), >50(2-12 months) and >40(1-5 years) in a child with cough, cold or fever singly or in combination was considered the criteria for recognition of pneumonia. Other parameters like previous episodes, family history of ARI and immunization status were also taken into account.Results: Out of the 145 children with ARI surveyed, 69.7% had LRTI while 30.3% had URTI. 63.4% male children and 36.6% female children had ARI; male: female ratio being 1.7:1. It was more predominant in the age group of 6-12 months (46.2%). Out of the 32 children not breast fed, 75% had LRTI and 25% had URTI. 31.7% of the children had previous episodes of ARI while 11% of the children had positive family history of ARI.Conclusion: An understanding of ARI prevalence and the associated risk factors is essential. There is a significant association between ARI and low socioeconomic status, overcrowding, low birth weight, delay in the initiation of breast feeding, lack of exclusive breast feeding, prelacteal feeding, timely given complementary feeding and immunization status. The importance of basic health promotional measures like proper infant feeding practices, proper nutrition, immunization and improvement in the socioeconomic status help in the control and prevention of ARI.